Edge Connectivity Problems in Telecommunication Networks - Antonius Suhartomo (Journal of ICT Research and Applications, 2012)
If a communication network N with n stations has every station linked with  at  least [n/2] other  stations,  then the  edge-connectivity  of  N  equals  its minimum  degree.  Also, in  general,  this  limitation  is  stated  to  be  the  best possibility,  as  was  proved  by  Chartrand  in  1966.  A  more developed  notion  of edge-connectivity  is  introduced, which  is  called  k-component  order  edge connectivity. It  is the minimum number of edges required to be removed so that the order of each disconnected component is less than k.